The Role of Daily Measurement of Lower Limb Circumference in Early Diagnosis of Deep Vein Thrombosis in the Presence of Other Risk Factors in Patients Admitted to Infectious Diseases Ward of Imam Reza Hospital, Mashhad, during 2012-2013 - Ali Akbar Heydari; Rryhane Jafari; Amin Bojdy; Mehrdad Farokhnia; Javad Ghaboulishahroodi; Ahmad Khalifeh Soltani; Hamid Reza Naderi; Mohammad Reza Sarvghad; Ashraf Tavanaee Sani (Patient Safety and Quality Improvement Journal, 2015)
Introduction: Considering the high rate of mortality in patients with Deep Vein Thrombosis (DVT) and pulmonary embolism, the aim of this study was to evaluate the role of daily measurement of lower limb circumference in early diagnosis of DVT in patients admitted to Infectious Diseases Ward of Imam Reza Hospital, Mashhad, during 2012-2013. Materials and Methods: This cross-sectional study was conducted in Infectious Diseases Ward of Imam Reza Hospital of Mashhad, Iran. Patients were divided into two age- and gender-matched groups. In the first group, the difference between the two legs was greater than 1 cm and in the second group it was 3 cm or more. Circumference of the two legs was assessed on a daily basis at 10 cm above tibial tuberosity. Doppler sonography was performed to rule out DVT. Data were analyzed using SPSS, Version 16. Results:A total of 204 patients were enrolled in this study, 18 of whom (8/8%) were diagnosed with DVT through Doppler sonography. In addition, 17 patients (11/3%) had fever as a comorbidity. Mean difference of the two legs was more than 3 cm in 16 DVT patients (14%), and two patients with mean difference of less than 3 cm had DVT. Conclusion: Daily measurement of lower limb circumference was an accurate and cost-effective technique for early diagnosis of DVT.